2010
DOI: 10.1177/1087057110380743
|View full text |Cite
|
Sign up to set email alerts
|

Development of Predictive Quantitative Structure-Activity Relationship Models of Epipodophyllotoxin Derivatives

Abstract: Epipodophyllotoxins are the most important anticancer drugs used in chemotherapy for various types of cancers. To further, improve their clinical efficacy a large number of epipodophyllotoxin derivatives have been synthesized and tested over the years. In this study, a quantitative structure-activity relationship (QSAR) model has been developed between percentage of cellular protein-DNA complex formation and structural properties by considering a data set of 130 epipodophyllotoxin analogues. A systematic stepw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The Q 2 value of all the hypothesis are greater than 0.55, F-test values are very high. High is necessary, the best QSAR model should be chosen based on its predictive ability, so the best model should have high Q 2 value also [24].…”
Section: Pharmacophore Model Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Q 2 value of all the hypothesis are greater than 0.55, F-test values are very high. High is necessary, the best QSAR model should be chosen based on its predictive ability, so the best model should have high Q 2 value also [24].…”
Section: Pharmacophore Model Generationmentioning
confidence: 99%
“…A large F indicates that the model fit is not a chance occurrence. It has been shown that a high value of statistical characteristics is not necessary for the proof of a highly predictive model [24]. Hence, in order to evaluate the predictive ability of our QSAR model the values of the of the correlation coefficient of predicted and actual activities and the correlation coefficient for regressions through the origin (predicted vs. actual activities and vice versa) were calculated and a score value of 0.76 for the test set and a score value of 0.86 for the training set were obtained, which is similar to [23].…”
Section: Validation Of Qsar Prediction Modelmentioning
confidence: 99%
“…The multi-target model based on Balaban index (J), a LUMO parameter, and second order valence connectivity index ( 2 χ v ) was very useful to describe the antimicrobial activity of synthesized compounds. Naik, Dubey, and Kumar [31], developed new predictive models for epipodophyllotoxin derivatives. Epipodophyllotoxins are important anticancer drugs used in chemotherapy for various types of cancers.…”
Section: Applications Of Molecular Informaticsmentioning
confidence: 99%